Molecular mechanism of Bushen Huatan Prescription in the treatment of Polycystic ovary syndrome based on network pharmacology and bioinformatics - Linhui Huang; Yu Huang; Qin Pang (Elsevier, 2022)
Polycystic ovary syndrome (PCOS) is a complex condition with reproductive, metabolic, and psychological symptoms. Because of the overlapping symptoms and its relation to multiple etiological factors, the disease is often difficult to diagnose and treat. The purpose of this study is to investigate the potential mechanism of Bushen Huatan Prescription (BHP) in the treatment of PCOS. First, the active ingredients and action targets of BHP were screened by retrieving the component data of the medicine in the following disease databases: Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform, Drug Bank, GeneCards, PCOS-related targets in Online Mendelian Inheritance in Man, PharmGKB, and UniProt. Next, the GEO database was searched for differently expressed targets. Then, the network of the association between BHP and PCOS components and targets was established, and a protein-protein interaction network was constructed using the screened key targets. Finally, the mechanism of BHP in the treatment of PCOS was obtained based on Gene Ontology function and Kyoto Encyclopedia of Genes and Genomes signaling pathway enrichment analysis. A total of 50 active ingredient monomers and 197 common targets of BHP in the treatment of PCOS were screened. It was found that BHP has multi-component, multi-target, and multi-pathway properties in the treatment of PCOS. It improves insulin resistance in obese PCOS patients by regulating the inflammatory microenvironment and boosts ovarian function by regulating the estrogen signaling pathway. We concluded that it provides new theoretical support for future research into the mechanism of BHP in the treatment of PCOS.